Perancangan Media Promosi Video Profil Mandana Mas Dengan Teknik Live Shoot Sebagai Upaya Meningkatkan Brand Awareness - Nathanael, Clemen Ogi; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
Mandana Mas is a company engaged in the fashion world that produce accessories made from beads. The purpose of designing this profile video media campaign is an effort to increase brand awareness of a perusaahan. Further research conducted with qualitative research methods that will conduct interviews, observation, documentation, and literacy in order to obtain the data used to support the design of Mandana Mas’s profile video. Keyword of designing video Mandana profile Mas've been through data analysis that has been done. Determining keywords is taken based on the data collected from interviews, observations, STP, literature studies, existing studies, and studies of competitors resulting in "Dynamic" as a keyword designing this profile video. The concept of "Dynamic" aims to demonstrate a business step of Mandana Mas who has integrity and innovative personality. So media video promotions and media profile supporter in the form of websites and product catalogs designed to give a picture of Mandana Mas information about working with integrity. Kata Kunci : Fashion, Accessories, Video Profile, Media Promotion, Brand Awareness.